Pengabdian Masyarakat Melalui Kegiatan Sosialisasi Tentang HIV/AIDS di MA Aliyah Swasta Nurul Huda Dowora Kota Tidore Kepulauan - Hairudin La Patilaiya (BAKTI : Jurnal Pengabdian Kepada Masyarakat, 2022)
Various steps to reduce the rate of death due to HIV / AIDS sufferers which are increasingly occurring in North Maluku in particular and in Indonesia in general, students must be provided with knowledge and understanding of the dangers of HIV / AIDS. School is one of the dedications / upbringing to convey this information, through schools it is hoped that information can be conveyed to students through education. The contribution of this activity is to increase public knowledge in general and adolescents in particular about the dangers of HIV / AIDS, as well as to help the Government disseminate PERDA number 4 of 2013 on HIV / AIDS prevention. The target that is wanted to be achieved is how to work together with the government to reduce the number of sufferers of this dangerous disease, in order to achieve a degree of health. With this activity, it is hoped that it will be able to increase the knowledge and understanding of students, as well as awareness of the dangers of HIV / AIDS and improve health information.